HAKIKAT MANUSIA DAN POTENSINYA MENURUT AL-QUR’AN DAN HADITS - Ahmad Yazid Hayatul Maky; Iskandar (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2021)
Humans are the noblest creatures in the sight of Allah swt in various fields, from form, behavior, communication, social interaction, to the establishment of applicable laws and connectedness with God. The Qur'an and Hadith in relation to Islamic Religious Education convey studies related to human nature and all its potentials that can be carried out by each individual human being for the benefit of himself, others and broader interests, to the level of becoming the best human profile in the version. Al Qur'an and human quality according to the study of Hadith. This article aims to find the meaning of Potential and Human Nature according to the Qur'an and Hadith. This writing method is in the form of a literature study (Library Research). The results of the writing describe that human nature has the basic meaning of Basyar (human with body dimensions), Insan (human with dimensions of growth and development), Bani adam (humans with hereditary dimension). The potential that exists in humans is the Instinct Potential (Emotional), Intellectual Potential (Intellectual), Sensory Potential (Physical), Religious Potential (Spiritual).